Distant Things: A Closer Look. Issue 50 (3rd July 2019) - Laasik, Kristjan
ABSTRACT: In a discussion of the constitutive role of colour in our visual perceptual experiences, Wilhelm Schapp centrally argues that we cannot visually perceive certain distant things, like a house seen far down in the valley. My main contention is that, in cases relevantly similar to Schapp's, we do perceptually experience distant things, viz., as drastically "decayed" things, which are part of distant scenes. In doing so, we adopt towards them a kind of conservative "attitude." The ideas of decay and scenicness will be unpacked in terms of the Husserlian ideas of fulfilment, and fulfilment conditions, capturing the idea that we perceptually experience objects in terms of anticipated possibilities for further experiences of these objects. These ideas will also be considered in relation to Herbert Leyendecker's notion of an attitude, e.g. of observing, searching for, or working with objects.